The regulation mechanism of AhR activated by benzo[a]pyrene for CYP expression are different between 2D and 3D culture of human lung cancer cells. Issue 4 (August 2018) - Terashima, Jun; Jimma, Yoko; Jimma, Keiko; Hakata, Shuko; Yachi, Maako; Habano, Wataru; Ozawa, Shogo
Abstract: Most of cytochrome P450 (CYP) expressions are regulated by nuclear receptors. The regulation pathways of transcription are activated by binding of the ligand to the receptor. Many combination of CYPs and nuclear receptors in transcriptional regulation have been reported. However, we have reported that the combination changes depending on culture condition on the same type of cells. The regulation pathway of CYP1A expression is different between 2D monolayer cultured cells and 3D spheroids of human liver cancer cells. Aryl hydrocarbon receptor (AhR) is one of the transcription factors for CYP1A and CYP1B1 expression, and this pathway is important for inducing human lung cancer. CYP1B1 expression in human lung cancer cells are regulated by AhR in 2D and 3D cells. But CYP1A expression are not induced by AhR in 3D cells. As with liver cancer cells, the function of AhR in lung cancer cells is different between 2D cells and 3D spheroids. These results important for understanding relationship between AhR and CYP expression before and after cell neoplastic formation in human lung. Graphical abstract: